2020
DOI: 10.1186/s13408-020-00086-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the dynamics of biological and neural oscillator networks through exact mean-field reductions: a review

Abstract: Many biological and neural systems can be seen as networks of interacting periodic processes. Importantly, their functionality, i.e., whether these networks can perform their function or not, depends on the emerging collective dynamics of the network. Synchrony of oscillations is one of the most prominent examples of such collective behavior and has been associated both with function and dysfunction. Understanding how network structure and interactions, as well as the microscopic properties of individual units… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
157
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 226 publications
(157 citation statements)
references
References 257 publications
(441 reference statements)
0
157
0
Order By: Relevance
“…This applies in particular for the linearisation of the WC model, another popular neuroscience model very different in essence from coupled oscillator models. In the thermodynamic limit and under certain assumptions about the distribution of oscillator frequencies, the Kuramoto model can be reduced to a two-dimensional system [43,44]. Our results are applicable to the linearisation of a fully desynchronised reduced Kuramoto model observed through X 1 = ρ cos θ where r = ρe iθ is the order parameter (ρ is the modulus and θ the angle in the complex plane).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This applies in particular for the linearisation of the WC model, another popular neuroscience model very different in essence from coupled oscillator models. In the thermodynamic limit and under certain assumptions about the distribution of oscillator frequencies, the Kuramoto model can be reduced to a two-dimensional system [43,44]. Our results are applicable to the linearisation of a fully desynchronised reduced Kuramoto model observed through X 1 = ρ cos θ where r = ρe iθ is the order parameter (ρ is the modulus and θ the angle in the complex plane).…”
Section: Discussionmentioning
confidence: 75%
“…If we pick values for β, E * and I * , the remaining parameters can be obtained by equating (44) and (45), and by re-arranging Eqs. (42) and (43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, other electrochemical systems and the BZ reaction can generate rich variety of clusters, in particular, when the sign of the coupling strength can also be varied (e.g., excitatory and inhibitory coupling) [31,39]. The weak chimera state could contribute to exploring chimeras in robust biological systems, e.g., circadian clocks [57], and dynamical diseases [58]; see also [59] for a recent review. Along these lines, we showed that an integrate-and-fire neuron model, with refractory period can generate bistability between cluster states in globally coupled populations [56].…”
Section: Resultsmentioning
confidence: 99%
“…2, is determined by both the amplitude and phase of the system, the expectation is that stimulation will lead to a change in both these quantities, which we refer to as the instantaneous amplitude and phase response of the system. To obtain analytical expressions for these quantities, we can consider an infinite system of oscillators satisfying the ansatz of Ott and Antonsen [26,27]. In our previous work [14], we showed that for a general nPRC given by Equation (12) and assuming the natural frequencies are Lorentzian distributed with centre ω 0 and width γ, the instantaneous change in the order parameter can be written as…”
Section: Reduced Kuramoto Modelmentioning
confidence: 99%